Phased Array Beam Steering Through Serial Control of the Phase Shifters - Randy L. Haupt , (Applied Computational Electromagnetics Society Journal (ACES), 2021)
The commands to control the phases shifters in a phased array can be sent through a parallel or serial channel. Parallel commands simultaneously change the phase shifters, allowing the beam to nearly instantaneously hop from one direction to another. If a serial channel is used, then the commands are sequentially sent to the phase shifters. The sequential approach causes the beam to gradually move from one position to another, rather than the quick hop encountered with a parallel channel. This paper shows simulated results of the behavior of the array factor due to serial phase shifting and effects the element sequence has on that behavior and a method to optimize the command sequence.